The analysis of online training, work productivity and employee relation for work from home employees in Metro Manila - Camarillo, Bridgette J.; Carrera, Mary Jane D.; Cielo, Judine; De Chavez, Wennie G.; Devinagracia, Dreiann H.; Rosagaran, Mary Joy T.; Galvan, Roschack V. 4 0 16; 5
ABSTRACT: The majority of people have already used work-from-home opportunities to reduce disease outbreaks and financial losses caused by COVID-19. The goal of the current study is to address the problems arising from work-from-home efficiency regarding online training, work productivity, and employee relations. This report is utilized quantitative research methodology to assess the efficiency of working from home during the pandemic. To address issues with the efficiency of online training analysis, work productivity, and employee relations for remote workers in Metro Manila, Researchers conducted a survey questionnaire separated into four (4) parts and recruited seventy-four (74) respondents. After the data gathering procedure and data analysis, the researchers rejected their null hypothesis and found that there is a significant moderate positive correlation between online training, work productivity, and employee relations with regard to the efficiency of working from home. The researchers also concluded that only work productivity exhibits a significant relationship with the quality and efficiency of working from home.
Research Paper: (BSBA major in Human Resource Management and Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2